2004
DOI: 10.1177/026119290403201s16
|View full text |Cite
|
Sign up to set email alerts
|

Rat Hepatocyte Suspensions as a SuitableIn VitroModel for Studying the Biotransformation of Histone Deacetylase Inhibitors

Abstract: This paper focuses on the use of liver-derived in vitro systems for biotransformation studies during early drug development, as exemplified by the two molecules recently studied in our laboratory: Trichostatin A (TSA) and its structural analogue 5-(4-dimethylaminobenzoyl)aminovaleric acid hydroxamide (4-Me2N-BAVAH). Phase I biotransformation of TSA, a histone deacetylase inhibitor with promising antifibrotic and antitumoural properties, was investigated in liver microsomal (rat and human) and in hepatocyte (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Lack of N-acetylation of the hydroxylated aniline metabolites in the dog is consistent with the absence of N-acetyl transferases in dogs [13]. Reduction of vorinostat to the corresponding amide moiety has been noted as a significant metabolic pathway in vivo and in vitro for some hydroxamic acids, e.g., 4-arylsulfonylpiperidine-4-hydroxamic acid [14] and Trichostatin A [12]; however, it was not a significant pathway in the metabolism of vorinostat.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Lack of N-acetylation of the hydroxylated aniline metabolites in the dog is consistent with the absence of N-acetyl transferases in dogs [13]. Reduction of vorinostat to the corresponding amide moiety has been noted as a significant metabolic pathway in vivo and in vitro for some hydroxamic acids, e.g., 4-arylsulfonylpiperidine-4-hydroxamic acid [14] and Trichostatin A [12]; however, it was not a significant pathway in the metabolism of vorinostat.…”
Section: Discussionsupporting
confidence: 54%
“…It was demonstrated that the majority of the total radioactivity was associated with the -oxidation products 6-AOH and 4-AOB, sug- gesting that hydrolysis to the acid followed by -oxidation dominates the biotransformation of vorinostat in preclinical species. Hydrolysis of the parent molecule to form the corresponding acid has been observed with other hydroxamic acids e.g., VRC4232, a peptide deformylase inhibitor with antibacterial activity [11] as well as with Trichostatin A, an HDAC inhibitor [12]. It is not surprising that, following hydrolysis of vorinostat, the 8-AOO metabolite undergoes extensive -oxidation as this metabolite is a semianilide of a medium chain dicarboxylic acid and, as such, would be prone to metabolism by -oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring cyclic tetrapeptide antibiotics including Trapoxins, for example, are very potent inhibitors of purified HDAC, but show a very weak activity in the animal in vivo [390] due to chemical instability of the epoxide in the blood [139]. Likewise, using primary hepatocytes and microsomal fractions of human and rodent origin, we observed that the natural hydroxamic acid TSA [379,387], like some of its synthetic analogues (SAHA [386]), is characterized by a low metabolic stability. Inactive TSA metabolites were produced both in vitro [379,387] and in vivo [380].…”
Section: Adme Propertiesmentioning
confidence: 99%
“…The use of TSA as a differentiating agent is limited due to its rapid and complete biotransformation, and thus inactivation, by the hepatocytes [173]. This inspired a search for metabolically more stable compounds, which resulted in the synthesis of benzamide-based TSA analogues [174].…”
Section: Hdac Inhibitors: Differentiating Agents For Primary Hepatocymentioning
confidence: 99%